Analisis Penentuan Harga Pokok Produksi Dengan Metode Full Costing Dalam Penentuan Harga Jual Pada Usaha UMKM Ayam Penyet Syakilah - Mawarni, Dila Putri; Irfan, Andi (Program Studi Ekonomi Syariah Fakultas Agama Islam Universitas Pahlawan Tuanku Tambusai, 2024)
The aim of this research is to determine the cost of production based on the method practiced by MSMEs and the Full Costing method, to compare selling prices between the MSME method and the Full Costing method, as well as preparing a profit and loss report based on the MSME and Full Costing methods. The method used in this research is descriptive qualitative by collecting data from interviews, observation and documentation. The informants in the research were the owner, cashier, chef and waiter. Data analysis techniques used in determining the cost of production using the Full Costing method. The results of this research are that in determining the cost of production based on the MSME method, factory overhead costs are not taken into account in detail, while the full costing method takes fixed factory overhead costs into account in detail. Comparison of selling prices using the full costing method is higher than that of MSMEs and the profit and loss report also shows that net profit at full costing is higher compared to the MSME method